Groundwater quality assessment of north of Iran (Golestan Province) using multivariate factor analysis and GIS techniques. Issue 6 (1st June 2022) - Nassiri, Mohammad; Mehdinejad, Mohammad Hadi
Abstract: Groundwater is one of the most important sources of drinking water. Since the quality of water directly influences consumers' health, it is essential to assess the quality of water and related factors. This descriptive-analytical study was performed on physical and chemical variables of water samples collected in the dry and wet seasons during 2006–2020 period. Changes in groundwater quality were investigated by factor analysis (FA) model and geographic information system (GIS) software. Based on factor analysis model, EC, TDS, TH and Mg +2 levels were the most important factors affecting the quality of water. Due to the high level of hardness (dry seasons; 389.4 mg/l and wet seasons; 418.4 mg/l) and sodium in water (dry seasons; 138 mg/l and wet seasons; 158 mg/l), necessary measures should be taken before drinking and agriculture uses. Changes in the water quality were more related to natural factors and human activities. The invasion of saline water into the groundwater aquifers in the study area should be considered. HIGHLIGHTS: The high water hardness. Increasing the concentration of elements during these years in two region. The ranks of abundance of the ions are as follows: anions including > > Cl − and cations including Ca 2+ > Mg 2+ > Na + > K + . The higher risk of water invasion in Aghghala region in comparison with Gorgan region. Consistency of application of these two methods to analyze water quality data.